Responsiveness of the International Classification of Functioning, Disability And Health (ICF) Clinical Functioning Information Tool (ClinFIT) in Routine Clinical Practice in an Australian Inpatient Rehabilitation Setting - Bhasker Amatya; Alaeldin Elmalik; Krystal Song; Su Yi Lee; Mary P Galea; Fary Khan (Medical Journals Sweden, 2022)
Objective: To examine the responsiveness of the International Classification of Functioning, Disability and Health (ICF) Clinical Functioning Information Tool (ClinFIT) in routine clinical practice in an Australian context. Methods: A prospective observational study with consecutive recruitment of inpatients at a tertiary rehabilitation facility. The assessments were at admission (T0), discharge (T1) and 3-month postdischarge (T2), using the following questionnaires: ClinFIT, Functional Independence Measure (FIM) and European Quality of Life (EQ-5D-5L). Extension Indices (EI) were calculated for the ClinFIT set, and responsiveness measured as a change in scores over time. The association between FIM and ClinFIT scores was explored. Results: Participants (n = 91, mean age 66.8±13.0 years, 52% male, 48% following stroke) reported ≥ 1 issue related to ClinFIT categories. ClinFIT total raw scores improved significantly across all health conditions compared with T0 (median (interquartile range): 196 (110, 228)) at both T1: 69 (37, 110); p < 0.001 and T2: 46.5 (20.8, 77); p < 0.001, with a medium effect size (r = 0.61 for both). There were significant changes in EI in the entire ClinFIT set from T0 to T1, and from T0 to T2 (p < 0.001 for both), with small to medium effect sizes. Analyses confirmed significant correlation in improvements between ClinFIT and FIM scores. Conclusion: ClinFIT is useful in evaluating patient functioning and can detect changes in functioning over time and across different health conditions. LAY ABSTRACT Regular patient evaluation and clinical assessment is needed to maximize positive outcomes from rehabilitation intervention. This prospective study assessed the responsiveness of the International Classification of Functioning, Disability and Health (ICF) - Clinical Functioning Information Tool (ClinFIT) for the assessment of functioning in an inpatient rehabilitation facility in Australia. Overall, 91 patients with different health conditions (majority with stroke) were assessed at admission, discharge, and at 3 months after discharge, using the ClinFIT set, and compared with another routinely used instruments, the Functional Independence Measure (FIM). The findings showed that the ClinFIT set is useful in evaluating patients' functioning over time across different health conditions.